PENGARUH DAYA TARIK WISATA, PERSEPSI HARGA DAN CITRA DESTINASI TERHADAP KEPUTUSAN BERKUNJUNG KE FLOATING MARKET LEMBANG - Putri Gumay; Sinthon Siahaan (Panorama Nusantara, 2022)
The purpose of this research to analyze the effect of tourist attraction, price perception, and destination image on tourist decisions to visit Lembang Floating Market. The population used are visitors to the Lembang Floating Market. Data collection was done by distributing questionnaires to visitors using purposive sampling method to get 100 respondents. The data analysis method used in this study is multiple regression analysis using SPSS 20 for Windows. The results of the study stated that (1) Simultaneously, tourist attraction, price perception and destination image had a positive and significant effect on tourist decisions to visit Floating Market Lembang by 53.3%. (2) Partially, tourist attraction has a positive but not significant effect on the decision to visit the Lembang Floating Market. (3) Partially, variable price perception has a positive and significant effect on the decision to visit the Lembang Floating Market; (4) Partially, destination image variable has a positive and significant effect on the decision to visit the Lembang Floating Market.